Development of Audio Video Media Based on Discovery Learning for Automotive Vocational School Students - Aci Primartadi; Arif Susanto; Fathoni Rosyid Alhaq; Dedi Irawan; Septian Adi Wijaya (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This study aims to develop Audio video media based on the discovery learning model. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study consisted of 3 media experts, 3 material experts, teachers and 24 students of SMK Otomtif. The data collection methods used consisted of observation, interviews, documentation, questionnaires, posttests, and performance with qualitative and quantitative data analysis techniques. Based on the results of the study, a review from media experts showed a percentage of 92% (very good), material experts 95% (very good), teacher questionnaires 97% (very good), student questionnaires 99% (very good), posttests using multiple choice questions. Based on the results of the analysis, video media based on the discovery model is effective for learning the theory of SMK Otomtif students.